A Lightweight Container Middleware for Edge Cloud Architectures - Leon, David; Miori, Lorenzo; Sanin, Julian; El Ioini, Nabil; Helmer, Sven; Pahl, Claus (Fog and Edge Computing, 2019)
Containers form the basis of a middleware platform that suits the needs of platform‐as‐a‐service (PaaS) clouds, where application packaging and orchestration are key issues. This chapter introduces architecture requirements and review technologies and architectures for edge clouds. It discusses core principles of an edge cloud reference architecture that is based on containers as the packaging and distribution mechanism. The chapter presents different options for storage, orchestration, and cluster management for distributed clusters in edge cloud environments. It provides a report on experimental results with Raspberry Pi clusters to validate the proposed architectural solution. The settings included are: an own‐build storage and cluster orchestration; an OpenStack storage solution; Docker container orchestration; and Internet of Things (IoT)/sensor integration. The chapter also includes practical concerns such as installation and management efforts, since lightweight edge clusters are meant to be run in remote areas.